Beyond their nutritional value, school meal programs support agricultural and food transition toward sustainability by creating multi-sectoral values in France - Avallone, Sylvie; Nicklaus, Sophie; Giner, Céline; Cohen, Juliana F. W.; Verguet, Stéphane (Frontiers in Nutrition, 2025)
The COVID pandemic has highlighted the essential role of school meal programs, not only for education but also for children’s nutrition. In France, school meals are shaped by ambitious policies to ensure their safety and nutritional quality, while promoting sustainable eating practices and awareness of environmental and agricultural challenges. In this article, we used the case study of France to discuss the multi-sectoral value of these programs. The economic value of school meals in France amounts to €8.2 billion annually, of which 2.8 billion are dedicated to food purchases. Since 2022, the EGAlim and Climate and Resilience laws require canteens to offer one vegetarian meal per week and to source at least 50% of sustainable products with positive environmental or social impacts (e.g., certified products, organic farming, and short supply chains). These laws represent a potential support of €1.4 billion for more sustainable agriculture. School canteens also offer a unique opportunity for food education, allowing children to discover new types of food, notably with vegetarian menus. They can contribute to preventing childhood obesity by reducing exposure to ultra-processed foods. Additionally, they play an important role in social inclusion by providing subsidized meals for disadvantaged children. However, disparities in access to canteens persist due to the cost of meals, dietary restrictions or the presence of a parent at home. In conclusion, school meal programs in France generate significant multi-sectoral value in the areas of education, nutrition, agriculture, and social inclusion and support the transition to more sustainable food systems for future generations.